Formula for growth:
y = initial • (percent growth + 1)^time/frequency of growth
So, since initial population is 382
Percent growth is 0.007
The time is 30 years
And it goes it by .07% every 1 year,
y = 382 • (1.007)^30/1
y= 470.9203732 people
Since we can’t have 0.9 of a person, the population after 30 years will be 470 people.
Answer:
irrational because the square root of 51 is irrational.
Answer:
y = -2x - 6
Step-by-step explanation:
Find the gradient: y difference/x difference
0 - (-6) / -3 - 0
6 / -3
= -2
y = mx + c
-6 = -2 × 0 + c
-6 = c
= C = -6
There are a couple of operations you can do on powers
We can multiply powers with the same base
x4⋅x2=(x⋅x⋅x⋅x)⋅(x⋅x)=x6
xa⋅xb=xa+b
This is an example of the product of powers property tells us that when you multiply powers with the same base you just have to add the exponents